Pengaruh Dukungan Endorser Dan Brand Familiarity Terhadap Perception Of Purchase Risk Dan Dampaknya Pada Niat Beli Produk Brand Extension - Lialutfi Mayangsari; Y. Lilik Rudianto (Universitas Airlangga, 2014)
At this time, the firms faced tight competition. The firms expected to manage the resources possessed to be able to win the competition. One method used to develop the brand with the expansion of related or unrelated to the parent brand. This strategy is done by utilizing the parent brand advertising campaign media. In the advertising, usually raises the figure endorser such as a celebrityor not to display the endorser with a familiar brand or unfamiliar brand. By looking at the ads with display support different endorser and brands make different consumer response to the perception of risk purchase that ultimately led to purchase intention the product extension.This study was conducted to investigate the effect of endorser support and brand familiarity to perception of purchase risk and its impact on purchase intention of brand extension products. This study tried to see the main effect of the variables and its interactions with the effect that using a factorial experimental design 2 (endorser support) x 2 (brand familiarity) with between subject methods. Data were obtained from 120 respondents who are students of S1 Management Faculty of Economics and Business, University of Airlangga.The analysis showed that there were no significant difference from the endorser support and there are significant differences from the brand familiarity on perception of purchase risk and there is no interaction effect between the endorser support and brand familiarity for reduces the perception of risk perceived by consumers. Perception of risk purchase also significantly influence consumer purchase intentions on the product brand extension.